Layanan Konseling dan Dukungan Psikologi di Kecamatan Selebar - Triyani Pudjiastuti; Selvina Margareta; Ath Thoriq Mulyawan Perdana Arisandi; Bayu Brhawijaya; Rika Afriyani; Juita Aprianti (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) Community Service Program implemented in Selebar Sub-District aims to enhance mental health awareness and literacy among adolescents through an Islamic Guidance and Counseling approach. Adolescents are a vulnerable group facing emotional, social, and academic pressures, necessitating adequate psychological support. Students from the Islamic Guidance and Counseling Study Program at UIN Fatmawati Sukarno Bengkulu carried out this program using the Participatory Action Research (PAR) method, which included activities such as individual counseling, group guidance, and education on stress management, mindfulness, and self-care. The program engaged local communities, Islamic boarding schools, and religious institutions as partners in outreach and spiritual assistance. This initiative highlights the students’ role as social change agents capable of responding to societal needs through a holistic approach grounded in Islamic values. Evaluations indicated an increase in participants’ understanding of the importance of mental health, a reduction in stigma toward counseling, and greater willingness to seek professional help. The success of this program positively impacted adolescents' psychological well-being and reinforced the role of higher education institutions in building mentally and spiritually empowered communities. This experience provided meaningful learning for students, integrating academic knowledge with real-world social needs through transformative community engagement.